A importância da experimentação no ensino de ciências nas séries iniciais do ensino fundamental - SANTOS, Josineide das Graças Fonseca dos (2024)
This study was conducted in the municipality of Abaetetuba Pará State , to identify whether the practical activities are part of the process of Teaching and Learning of Students of Elementary Education School Joaquim Mendes Content . Initially we carried out a literature search on the Importance of experimentation in science teaching in the early grades of elementary school. In a second step we carried out a field survey using two questionnaires as tools to teachers and students of the fourth year of classes " A" and fourth grade " B " and fifth grade " A" and " B " of that school . The questionnaire used for Teachers is divided into three stages , which address issues related to science teaching , training concepts and teaching strategies in order to highlight the difficulties that teachers face when using allege experimentation in their daily work as well as the need for reflection on the part of those on the use of the methodology of experimentation as an efficient strategy to develop students who can scientific reasoning and encouraging the spirit of investigation for understanding of the laws and phenomena of science . The other questionnaire used in this research was targeted at students of these four classes , in order to inquire them about the acceptance of the experimental activity and the contributions from the process of teaching / learning caused by the use of the same . As part of the process of data collection were developed with students experiential activities related to the content already covered this school year . Activities using alternative materials and were carried out in the classroom . The analysis of the survey results are reported in the Results and Discussions of this work completion full degree course in Natural Sciences.